Household dampness and microbial exposure related to allergy and respiratory health in Danish adults. Issue 1 (1st January 2020) - Juel Holst, G.; Pørneki, Ad; Lindgreen, J.; Thuesen, B.; Bønløkke, J.; Hyvärinen, A.; Elholm, G.; Østergaard, K.; Loft, S.; Brooks, C.; Douwes, J.; Linneberg, A.; et al.
ABSTRACT: Background: Indoor dampness has consistently been associated with respiratory symptoms and exacerbations. The causal mechanisms may involve increased microbial exposures. However, the evidence regarding the influence of indoor microbial exposures under damp- and non-damp conditions on the risk of asthma and allergy has been inconclusive. Objective: The aim of this study was to investigate the association between dampness and microbial exposure with allergy and respiratory health in Danish adults using a cross-sectional design. Methods: From 1, 866 participants of the Health2006 cohort, we selected three non-overlapping groups: 196 at random, 107 with confirmed atopy, and 99 without atopy. Bedroom dust was sampled using electrostatic dust fall collectors and analysed for endotoxin, β-(1, 3)-D-glucan, 19 microbial species or groups, and total fungal load. Household moisture-related problems and asthma were self-reported by questionnaire. Atopy was determined by skin-prick-testing and lung function was measured by spirometry. Results: Household moisture damage was positively associated with asthma outcomes, although this was statistically significant only in atopics for self-reported asthma (odds ratio (OR) 3.52; 95%CI 1.01–12.7). Mould odor was positively associated with wheezing (OR 6.05; 95%CI 1.19–30.7) in atopics. Inconsistent associations were found for individual microbial exposures and health outcomes. Inverse associations were observed between microbial diversity and rhinitis in the random sample and both doctor-diagnosed and self-reported asthma in non-atopics. Conclusions: In conclusion, our findings suggest that household moisture damage may increase the risk of asthma and wheeze with mould odor in atopics. In addition, asthma and allergy may be affected by the indoor microbial composition in urban domestic environments. Further studies are needed to identify and understand the causal agents and underlying mechanisms behind the potential effects of environmental microbial exposure on human health.